2021
DOI: 10.1590/1980-549720210013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on Prenatal, Diabetes and medical appointments in the Brazilian National Health System

Abstract: Objectives: The purpose of this study was to describe the impact of the COVID-19 pandemic on Primary Health Care in Brazil. Methodology: This retrospective ecological study was carried out using Brazilian municipality data obtained from the information systems of the National Public Health System. The outcomes were medical appointments, prenatal procedures and diabetes care. The exposure variable was the occurrence of the COVID-19 pandemic, based on the first case reported in Brazil. Multilevel mixed-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
0
15
0
8
Order By: Relevance
“…Even though the reduction at the beginning of the pandemic was considerable, when the exponential growth took off, the systems almost suffered a shutdown. 20,27,28,29 A national online survey with more than 3,000 dentists from all regions found that more than 95% of those interviewed had reduced the number of patients they were seeing or were only attending emergencies or were not attending at all. 30 Also, there was a difference between dentists working in public and private networks.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the reduction at the beginning of the pandemic was considerable, when the exponential growth took off, the systems almost suffered a shutdown. 20,27,28,29 A national online survey with more than 3,000 dentists from all regions found that more than 95% of those interviewed had reduced the number of patients they were seeing or were only attending emergencies or were not attending at all. 30 Also, there was a difference between dentists working in public and private networks.…”
Section: Discussionmentioning
confidence: 99%
“…Pressupõe assim, a prestação de cuidados centrados na pessoa e fundamentados na clínica ampliada. Um dos principais agravantes da pandemia foi a interrupção total ou parcial da prestação dos serviços de saúde destinados a outras condições que não a COVID-19 47 . Malta et al 48 identificaram dificuldades para utilização de serviços de saúde entre pessoas com DCNT e destacam que isto pode ser explicado, entre outros fatores, pela menor oferta de serviços pelos setores de saúde público e privado durante a pandemia.…”
Section: Resposta Sindêmica E Políticas De Saúdeunclassified
“…Tal decréscimo medidas podem levar a danos não intencionais que são potencialmente maiores do que aquele que pretendia evitar. Esse resultado também é reflexo da pesquisa realizada por Chisini et al (2021) em 5.570 municípios brasileiros sobre os impactos da pandemia de COVID-19 no pré-natal no Sistema Único de Saúde, em que houve um declínio em mais de 50% da assistência pré-natal durante a pandemia, comparado ao contexto não pandêmico.…”
Section: Resultsunclassified
“…⠀⠀⠀⠀⠀⠀Perante a esse contexto, percebe-se que serviços essenciais na assistência à saúde infantil, que já começa desde o pré-natal, sofreram impactos significantes dentro de um cenário de incerteza que foi evidenciado pela pandemia da COVID-19, onde as atenções estavam voltadas para uma patologia em que pouco conhecimento existia sobre ela. Além disso, os sistemas de saúde no Brasil e no mundo não estavam preparados para enfrentar essa nova realidade, o que foi refletido na queda da assistência em todos os níveis de atenção (MENENDEZ et al, 2020;CHISINI et al, 2021).…”
Section: Impactos Nosunclassified